New record of six Brachionus species from the South of Iraq - Hassan, Hala F.; Ali, Malik H.; Al-Badran, Adnan I. (Iraqi Journal of Aquaculture, 2023)
In this survey, six species of Brachionus genus are indexed as new record in the south Iraqi water resource at the first time in Iraq depending on the sequence of 18S rRNA gene, these species were registered as a new record in Iraq and the other two species which are HH1 and HH2 were registered in the National Center for Biotechnology Information (NCBI), The European Nucleotide Archive (ENA) and DNA Data Bank of Japan (DDBJ) sequentially.